CLASSIFICATION OF THE STAFF OF THE STATE BUREAU OF INVESTIGATIONS OF UKRAINE (BASED ON THE ANALYSIS OF ITS STAFF AND ORGANIZATIONAL STRUCTURE) (Bulletin of criminological association of Ukraine, 2023)
The article proposes the author's vision of the classification of the personnel of the State Bureau of Investigation according to the following criteria:professional affiliation, i.e. a specific type of work, the implementation of which requires qualifications, a set of theoretical and practical skills and/or specialization (lawyers, law enforcement officers, economists, engineers, psychologists, etc.). etc.); the level of qualification, which determines the degree of readiness of the employee to perform professional functions and depends on the presence or absence of diplomas on education, advanced training, work experience (highly qualified, qualified, low-qualified and unqualified); position (director, first deputy director, deputy directors, heads of departments and their deputies, heads of departments and their deputies, detectives, senior operational officers and operational officers, inspectors, etc.); legal position in the management system: officials, government representatives, workers, etc.; functional direction of professional activity (management, specialists, employees, workers, etc.). Also, based on the characteristics of the organizational and staff structure of the State Bureau of Investigation and the division carried out, its staff (in a broad sense) is defined as a set of persons who, on a permanent or temporary basis, undergo state (public) service, performing professional activities in the central apparatus, its territorial offices , as well as other institutions of the State Bureau of Investigation and will receive financial support or wages for this (if they work under the terms of a tour contract).
Keywords: public service; personnel; public servants; public servants; service; State Bureau of Investigation